Adding an unnatural covalent bond to proteins through proximity-enhanced bioreactivity - Xiang, Zheng; Ren, Haiyan; Hu, Ying S; Coin, Irene; Wei, Jing; Cang, Hu; Wang, Lei (Nature methods, 2013)
An unnatural amino acid that forms a covalent bond with a proximal cysteine can be introduced into proteins, facilitating a variety of applications. Natural proteins often rely on the disulfide bond to covalently link side chains. Here we genetically introduce a new type of covalent bond into proteins by enabling an unnatural amino acid to react with a proximal cysteine. We demonstrate the utility of this bond for enabling irreversible binding between an affibody and its protein substrate, capturing peptide-protein interactions in mammalian cells, and improving the photon output of fluorescent proteins.